The Effectiveness of a Guided Education Program on the Skill and Attitude to Breastfeeding among First-Time Mothers in Jordan - Al-Radaydah, Dana; Badrin, Salwismawati; Badrin, Salziyan; Ismail, Tengku (Jordan Medical Journal, 2022)
Background: Although the benefits of breastfeeding have been well documented, the rate of breastfeeding in Jordan has recently decreased. Objective: This study aimed to determine the effectiveness of a guided breastfeeding education program on the breastfeeding skills and attitude towards breastfeeding among Jordanian first-time mothers who were exclusively breastfeeding. Methods: A quasi-experimental design was used. The study recruited a convenient sample of 87 firsttime mothers (intervention = 44, control = 43) from Princess Badea’a Hospital (PBH) in Irbid, Jordan. Data were collected using the Iowa Infant Feeding Attitude Scale (IIFAS) and the LATCH Assessment Tool at the pre-intervention phase (within four hours postpartum) and at the postintervention phase (at eight weeks postpartum). Repeated measures ANOVA was used to analyze the differences in means between and within the groups. Results: The results showed a significant increase in breastfeeding skills and attitude towards breastfeeding in the intervention group compared to the control. Conclusion: Guided breastfeeding education with breastfeeding support can improve breastfeeding skill and reflect positively on the attitude towards breastfeeding, as well as increase the intention to exclusively breastfeed, especially among first-time mothers.Gene therapy